The Interaction among Insulin Resistance, Liver Fibrosis and Early Virological Response in Egyptian Patients with Chronic Hepatitis C - Dina H Ziada; Sherif El Saadany; Mohamed Enaba; Medhat Ghazy; Azza Hasan (Canadian Journal of Gastroenterology)
BACKGROUND: Hepatitis C virus (HCV) infection may induce insulin resistance (IR) irrespective of the severity of liver disease, and there is evidence of a central role for IR in failure to achieve sustained virological response (SVR) in HCV patients.